Dai contadini operai agli amenity migrants. L'eredità del socialismo e il futuro del ruralismo montano in Romania - Andrea Membretti; Bogdan Iancu (Revue de Géographie Alpine)
This article investigates the legacy of state socialism and the post-socialist transformation inside the Romanian Carpathians by reviewing sociological literature on new inhabitants of the Alps and anthropological literature on ruralism in Romania. Today, after a period spent adapting to socialist agricultural and industrial policies, several rural communities of the Carpathians are facing growing waves of amenity migrants and urban tourists. In 2015, in order to investigate the potential role of these dynamics relative to the resilience of mountain dwellers, we collected qualitative data by means of in-depth ethnographic interviews with Romanian academics, tourist entrepreneurs, residents of and immigrants to the mountain village of Fundata in Transylvania. We recognise amenity migration and rural tourism as important but also ambivalent and as driving change with respect to the interrelated socio-demographic local change. Whereas the Carpathians have been losing population dramatically since the 1990s, and the remaining population has aged, rural tourism has brought new permanent and temporary inhabitants (often young people) and significant economic resources. Together with accommodation infrastructure, tourism has transformed several mountain villages’ physical and cultural landscape. As cultural brokers and economic resource bearers, amenity migrants and tourists represent both a threat to and an opportunity for post-socialist territories, which are facing long-term socio-economic and demographic crises. As we will discuss in the conclusions of the paper, also with regard to ongoing transformations in the Alpine regions, it seems clear that one cannot ignore the relevance of these urban actors (nor of the renewed urban-rural connection) to the revitalisation of mountain areas.